2011
DOI: 10.1074/jbc.m111.261370
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Multifunctionality in a Vitamin B12-processing Enzyme

Abstract: An early step in the intracellular processing of vitamin B 12 involves CblC, which exhibits dual reactivity, catalyzing the reductive decyanation of cyanocobalamin (vitamin B 12 ), and the dealkylation of alkylcobalamins (e.g. methylcobalamin; MeCbl). Insights into how the CblC scaffold supports this chemical dichotomy have been unavailable despite it being the most common locus of patient mutations associated with inherited cobalamin disorders that manifest in both severe homocystinuria and methylmalonic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
138
1
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 80 publications
(168 citation statements)
references
References 26 publications
12
138
1
9
Order By: Relevance
“…Studies with the bovine isoform of MMACHC revealed that the reduced form of glutathione stabilizes MMACHC, suggesting that intracellular redox control could play a role in the regulation of the protein ' s lifetime [ 41 -44 ]. Koutmos [ 3 ] and Froese [ 45 ] glutathione-binding pocket up above the β -axial ligand position [ 45 ]. Importantly, the arginine-rich pocket comprises residues Arg161, Arg206 and Arg230 ( recombinant mutant Arg206Gln was insoluble suggesting a structural role for this residue, and that mutants Arg161Gln and Arg230Gln abolished GSH binding and dealkylase activity, which is a strong indication that these amino acid residues are critical for GSH binding [ 45 ].…”
Section: Biophysical and Structural Characterization Of The B 12 -Promentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with the bovine isoform of MMACHC revealed that the reduced form of glutathione stabilizes MMACHC, suggesting that intracellular redox control could play a role in the regulation of the protein ' s lifetime [ 41 -44 ]. Koutmos [ 3 ] and Froese [ 45 ] glutathione-binding pocket up above the β -axial ligand position [ 45 ]. Importantly, the arginine-rich pocket comprises residues Arg161, Arg206 and Arg230 ( recombinant mutant Arg206Gln was insoluble suggesting a structural role for this residue, and that mutants Arg161Gln and Arg230Gln abolished GSH binding and dealkylase activity, which is a strong indication that these amino acid residues are critical for GSH binding [ 45 ].…”
Section: Biophysical and Structural Characterization Of The B 12 -Promentioning
confidence: 99%
“…High mRNA levels were detected in fetal liver with lower levels being detected in spleen, lymph node, thymus and bone marrow, and no message was detected in peripheral blood leukocytes [ 34 ]. Work by Koutmos et al showed that a truncated form of cblC lacking the last 38 amino acid residues is predominantly expressed in most tissues [ 3 ]. Importantly, a comprehensive examination of the mitochondrion proteome identified MMACHC as one of its resident proteins [ 35 ].…”
Section: Cellular Processing Of B 12 : Mmachc (Cblc)mentioning
confidence: 99%
“…Two CblC variants, a full-length (32 kDa) and a truncated (26 kDa) form, have been reported in human fibroblasts and in murine tissue (35,36). The formation of the truncated CblC form is attributed to a predicted splicing variant (35).…”
Section: Early Steps In the Cytosolic Processing Of Cobalaminmentioning
confidence: 99%
“…Two CblC variants, a full-length (32 kDa) and a truncated (26 kDa) form, have been reported in human fibroblasts and in murine tissue (35,36). The formation of the truncated CblC form is attributed to a predicted splicing variant (35). Although the prevalence of the truncated CblC form is not known, the presence of the C-terminal domain diminishes the stability of human CblC and is not required for its function (35).…”
Section: Early Steps In the Cytosolic Processing Of Cobalaminmentioning
confidence: 99%
See 1 more Smart Citation